2020
DOI: 10.1371/journal.pone.0239215
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cytopenia and its associated factors among HIV infected adults on highly active antiretroviral therapy at Mehal Meda Hospital, North Shewa Zone, Ethiopia

Abstract: Background Cytopenias affect the outcomes of highly active anti-retroviral therapy that results in higher morbidity, mortality, and impaired quality of life. The purpose of this study was to assess the prevalence of cytopenia and its associated factors among HIV infected adults on highly active antiretroviral therapy at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
2
10
1
Order By: Relevance
“…These findings were similar to several studies that reported the leucopenia, neutropenia, and lymphopenia was more prevalent among patients with CD4 count <200 cells/µL. 2 , 3 , 16 The prevalence of leucopenia and lymphopenia with decreased CD4 count was significantly associated before initiation of ART, but it did not significantly associate after ART initiation, this may be due to ART bringing a statistical increment into the WBC count. 11 , 13 The present study revealed that patients on AZT-based ART regimen had a higher prevalence of leucopenia, neutropenia, and lymphopenia compared to TDF-based ART regimen.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These findings were similar to several studies that reported the leucopenia, neutropenia, and lymphopenia was more prevalent among patients with CD4 count <200 cells/µL. 2 , 3 , 16 The prevalence of leucopenia and lymphopenia with decreased CD4 count was significantly associated before initiation of ART, but it did not significantly associate after ART initiation, this may be due to ART bringing a statistical increment into the WBC count. 11 , 13 The present study revealed that patients on AZT-based ART regimen had a higher prevalence of leucopenia, neutropenia, and lymphopenia compared to TDF-based ART regimen.…”
Section: Discussionsupporting
confidence: 90%
“…This was in line with previous studies. 2,21 According to the present study, the prevalence of leucopenia, neutropenia, and lymphopenia were increased with decreasing in CD4 count both before and after the initiation of ART. Leucopenia, neutropenia, and lymphopenia were more prevalent among HIV-positive patients whose CD4 count was <200 cells/µL.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations